Influence of cheese making process on STEC bacteriophage release - Mangieri, Nicola; Vieira, Rui P.; Picozzi, Claudia (Frontiers in Microbiology, 2023)
Shiga toxin-producing Escherichia coli (STEC) are foodborne pathogens implicated in diseases including hemolytic uremic syndrome (HUS) and hemorrhagic colitis (HC). The main virulence factor are Shiga toxins; their production and secretion are by-products of the expression of late genes of prophages upon sub-lethal environmental stimuli exposure. Hence, the lysogenic prophage after a stress switch to lytic cycle spreading the Sstx -phages. In the present study, 35 STEC were screened for the presence and the ability to release Shiga toxin-encoding bacteriophages. Three bacterial strains showed signals of prophage presence both in plate and in PCR. Subsequently, these bacterial strains were subjected to stressors that simulate cheese manufacturing conditions: NaCl (1, 1.5 and 2% w/v), lactic acid (0.5, 1.5 and 3% v/v), anaerobic growth, pasteurization (72ºC for 15 sec), UV irradiation. The ability to release prophage was evaluated by Real Time qPCR. Induction of the prophages showed that the addition of NaCl at 1.5 and 2% significantly increased viral release compared to control. Conversely, the addition of lactic acid had a significant repressive effect. The other applied stressors had no significant effect in phage release according to the experimental conditions adopted.